1995
DOI: 10.1002/nme.1620380603
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional parallel unstructured grid generation

Abstract: SUMMARYAn algorithm for the parallel generation of 3-D unstructured grids is presented. The technique is an extension of the algorithm presented in Reference 21 for the 2-D case. The method uses a background grid as the means to separate spatially different regions, enabling the concurrent, parallel generation of elements in different domains and interdomain regions. The parallel 3-D grid generator was implemented and tested on the INTEL hypercube and Touchstone Delta parallel computers. The results obtained d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Possible candidates are the parallelized volume mesh generation algorithms based on octree, advancing front or Delaunay methods [19][20][21][22][23][24][25][26][27].…”
Section: Identify All Continuous Regionsmentioning
confidence: 99%
“…Possible candidates are the parallelized volume mesh generation algorithms based on octree, advancing front or Delaunay methods [19][20][21][22][23][24][25][26][27].…”
Section: Identify All Continuous Regionsmentioning
confidence: 99%
“…Loehner [25] has demonstrated the extension of the advancing front algorithm to produce tetrahedral elements on parallel platforms. Said et al [30] have shown parallel mesh generation using initial coarse meshing and decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Several years ago, the author and his colleagues introduced a parallel AFT based on the subdivision of the background grid [Löh92,Sho95]. While used for some demonstration runs, this scheme was not general enough for a production environment.…”
Section: Introductionmentioning
confidence: 99%
“…the introduction of a new element only affects (and is affected by) the immediate vicinity. This allows for the introduction of elements in parallel, provided that sufficient distance lies between them.Several years ago, the author and his colleagues introduced a parallel AFT based on the subdivision of the background grid [Löh92,Sho95]. While used for some demonstration runs, this scheme was not general enough for a production environment.…”
mentioning
confidence: 99%